How the European Union had Tried to Tackle Fake News and Disinformation with Soft Law and what Changed with the Digital Services Act? (Frontiers in Law, 2024)
The article shows snapshots from the history of fake news and terms and concepts to use in the field of information disorder (fake news, disinformation, misinformation) based on a thorough literature review. It describes that neither the analysis of only the the speaker’s side (the intention) nor the the recipient’s side (the impact) could not alone give a proper conceptual framework, but both should be used by the legislation to tackle these issues. With the viral misinformation through social media, it is clear that this poses new regulatory challenges and requires rapid-response frameworks suited to the digital age’s unique dynamics. In the European Union, the road was marked by the Code of Practice on Disinformation, and the article describes how the EU Digital Services Act (DSA) tries to tackle fake news and disinformation. The article gives some possible legal solutions also.